Running characteristics of the complementary heating system with solar energy-ground source heat pump and heating network - Hao, Hong; Xue, X. (Editorial Department of Journal of Shenyang Jianzhu University, 2014)
In order to relieve the energy crisis, comprehensive utilization of energy and improve energy efficiency, running characteristics of complementary heating system used solar energy-ground source heat pump and heating network in cold region were studied. Based on the transient simulation software TRNSYS, two simulation models of this complementary heating system were built for comparison of system running characteristics. By the first model, the circulating fluid was firstly flowed into the heat storage water tank; by the second model, the circulating fluid was firstly flowed into the underground buried pipe heat exchanger. Simulation results show that the total heat storage in the water tank by the first model is 134 858 kWh, which is more than the total heat storage(132 296 kWh) by the second model. The heat pump unit coefficient of performance(COP) by the second model is 4.06, it is more than the COP value(4.04) by the first model; the total heat transfer in the underground buried pipe by the second model is 201 149 kWh, it is more than the heat transfer(198 571 kWh) by the first model. It is concluded that the supply heat should be concentrated in the middle of December to the next year's mid-February, but at the beginning and the end of the heating time, the heating demand is less. If the solar energy is taken as a main of source, the first model should be adopted, in order to improve the collector heating and to ensure high efficiency. If the ground source heating is taken as a main of source, adopting the second model can effectively use solar energy for saving more electricity.